Association between circulating fibroblast growth factor 21 and mortality in end-stage renal disease - Kohara, Marina (PLoS One, 2017)
Fibroblast growth factor 21 (FGF21) is an endocrine factor that regulates glucose and lipid metabolism. Circulating FGF21 predicts cardiovascular events and mortality in type 2 diabetes mellitus, including early-stage chronic kidney disease, but its impact on clinical outcomes in end-stage renal disease (ESRD) patients remains unclear. This study enrolled 90 ESRD patients receiving chronic hemodialysis who were categorized into low- and high-FGF21 groups by the median value. We investigated the association between circulating FGF21 levels and the cardiovascular event and mortality during a median follow-up period of 64 months. A Kaplan-Meier analysis showed that the mortality rate was significantly higher in the high-FGF21 group than in the low-FGF21 group (28.3% vs. 9.1%, log-rank, P = 0.034), while the rate of cardiovascular events did not significantly differ between the two groups (30.4% vs. 22.7%, log-rank, P = 0.312). In multivariable Cox models adjusted a high FGF21 level was an independent predictor of all-cause mortality (hazard ratio: 3.98; 95% confidence interval: 1.39–14.27, P = 0.009). Higher circulating FGF21 levels were associated with a high mortality rate, but not cardiovascular events in patient with ESRD, suggesting that circulating FGF21 levels serve as a predictive marker for mortality in these subjects.